Factors influencing medication adherence in multi-ethnic Asian patients with chronic diseases in Singapore: A qualitative study - Yoon, Sungwon; Kwan, Yu Heng; Yap, Wei Liang; Lim, Zhui Ying; Phang, Jie Kie; Loo, Yu Xian; Aw, Junjie; Low, Lian Leng (Frontiers in Pharmacology, 2023)
Background: Poor medication adherence can lead to adverse health outcomes and increased healthcare costs. Although reasons for medication adherence have been widely studied, less is explored about factors affecting medication adherence for patients in non-Western healthcare setting and from Asian cultures. This study aimed to explore cultural perspectives on factors influencing medication adherence among patients with chronic diseases in a multi-ethnic Asian healthcare setting. Methods: We conducted a qualitative study involving in-depth interviews with patients with chronic conditions purposively recruited from a community hospital in Singapore until data saturation was achieved. A total of 25 patients participated in this study. Interviews were transcribed and thematically analyzed. Themes were subsequently mapped into the WHO Framework of Medication Adherence. Results: Participants commonly perceived that sides effects (therapy-related dimension), poor understanding of medication (patient-related dimension), limited knowledge of condition (patient-related dimension), forgetfulness (patient-related dimension) and language issues within a multi-ethnic healthcare context (health care team and system related dimension) as the main factors contributing to medication adherence. Importantly, medication adherence was influenced by cultural beliefs such as the notion of modern medicines as harms and fatalistic orientations towards escalation of doses and polypharmacy (patient-related dimension). Participants made various suggestions to foster adherence, including improved patient-physician communication, enhanced care coordination across providers, use of language familiar to patients, patient education and empowerment on the benefits of medication and medication adjustment. Conclusions: A wide range of factors influenced medication adherence, with therapy- and patient-related dimensions more pronounced compared to other dimensions. Findings demonstrated the importance of cultural beliefs that may influence medication adherence. Future efforts to improve medication adherence should consider a person-centered approach to foster more positive health expectations and self-efficacy on medication adherence, supplemented with routine reviews, development of pictograms and cultural competence training for healthcare professionals.